Primary pure large-cell neuroendocrine carcinoma of the ovary: A rare case report - Reena Yadav; Kanika Chopra; Nishtha Jaiswal; Shilpi Aggarwal (Wolters Kluwer Medknow Publications, 2022)
Primary pure large-cell neuroendocrine carcinoma is a rare entity with 17 cases reported till now. A 48-year-old, Para6 Live4, postmenopausal woman presented with complaints of pain abdomen, constipation for 6 months, and postmenopausal bleeding for 1 month. On per abdominal examination, an irregular, hard, fixed, and tender mass was felt in the pelvis corresponding to 32 weeks size gravid uterus. Her magnetic resonance imaging findings were suggestive of a large abdominopelvic mass of size 10.2 cm × 12.7 cm × 14.2 cm with inferior extension into the left adnexa and 3.1 cm × 2.2 cm × 2.1 cm right adnexal mass. Debulking surgery was done. The intraoperative findings were of a large abdominopelvic mass adhered to the sigmoid colon and retroperitoneal space. Histopathological and immunohistochemistry findings were suggestive of bilateral large-cell neuroendocrine carcinoma of ovaries with strong positive for Bcl2, CD56, NSE, PR, and P53. The patient was started on tablet etoposide as adjuvant treatment. After 5 months of primary surgery, contrast-enhanced computed tomography of the chest, abdomen, and pelvis revealed recurrence. She succumbed to her illness 6 months after primary surgery. Owing to its rarity and difficulty in diagnosis, it is suggested that all such cases should be registered at national level and critically analyzed to find the high risk and associated prognostic factors.